2022
DOI: 10.1073/pnas.2020901119
|View full text |Cite
|
Sign up to set email alerts
|

Separations of romantic relationships are experienced differently by initiators and noninitiators

Abstract: Significance In economic and sociological theory of divorce, the link between divorce consequences and the decision to divorce is central: A couple divorces if at least one spouse expects to improve their life by initiating divorce. The present study provides empirical evidence in support of this theoretical link: Separation initiators become better off in terms of subjective well-being after a separation, whereas noninitiators become worse off, before they eventually experience a full recovery. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…Longer-term effects, however, were biased downward when adjusting for future life events (mostly finding a new partner) indicating overcontrol bias when adopting a total control strategy. This is consistent with a recent analysis of effects of separation on well-being that showed more positive post-event trajectories if re-partnering occurred within a year (Brüning, 2022).…”
Section: Are Effect Estimates Of Life Events On Life Satisfaction Bia...supporting
confidence: 91%
See 1 more Smart Citation
“…Longer-term effects, however, were biased downward when adjusting for future life events (mostly finding a new partner) indicating overcontrol bias when adopting a total control strategy. This is consistent with a recent analysis of effects of separation on well-being that showed more positive post-event trajectories if re-partnering occurred within a year (Brüning, 2022).…”
Section: Are Effect Estimates Of Life Events On Life Satisfaction Bia...supporting
confidence: 91%
“…Conversely, separation, unemployment, death of partner, and death of child affected life satisfaction negatively. In line with previous studies, we found a short-term negative effect of separation on life satisfaction in the year after the event that was relatively similar for men and women (Brüning, 2022;Rhoades et al, 2011;. For first separation, there was also evidence for a decrease in the second year after the event.…”
Section: Negative Eventssupporting
confidence: 91%
“…CHANGE IN RELATIONSHIP SATISFACTION separation). Future research should examine the moderating role of initiator status on change in relationship satisfaction in relationships and across consecutive relationships (e.g., Brüning, 2022). Relatedly, this study does not provide information about the relationship processes that may explain the patterns of stability and change in satisfaction within and across relationships.…”
Section: Limitations and Future Directionsmentioning
confidence: 90%
“…Moreover, women conduct a larger share of emotional work in the marriage, making them more perceptive to unmet needs (Frisco & Williams, 2003; Umberson et al, 2015). Indeed, about 55–90% of all divorces are requested by women (Australia: Hewitt et al, 2006; France: Boigeol & Commaille, 1974; Germany: Brüning, 2022; the Netherlands: Kalmijn & Poortman, 2006; Sweden: Wadsby & Svedin, 1992; United States: Braver et al, 1994; Brinig & Allen, 2000; England et al, 2016; Rosenfeld, 2018; Sweeney, 2002). In line with the view of lower marital attractions for women, a recent study suggests that although women are more likely to desire and start the divorce process, men are more likely to be held responsible for the divorce (Parker et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%